Using New Testament Greek in Ministry : a practical guide for students and pastors - Black, David Alan, 1952- (Grand Rapids, Mich. : Baker Book House, 1993)
This book focuses on the transformation of exegesis into exposition, of studies into sermons. To prepare students toward this end, David Alan Black explains the process of using the Greek text and linguistic resources to study the New Testament, and he recommends a basic library of reference books. - Back cover
Includes bibliographical references (p. 121-124) and indexes.
Keywords: Bible. -- Versions; Bible. -- Homiletical use; Greek language, Biblical